How do the state's organisational capacities at the micro- and macro-levels influence agriculture-nutrition linkages in fragile contexts?. (January 2019) - Gupte, Jaideep; Longhurst, Richard
Highlights: Ag-nutrition linkages require special attention in fragile contexts in South Asia. There is a balance between what the state ought to do, can do and is willing to do. The state has to engage systemically and intersectorally, integrating sectors. State capacity must enhance the mobilisation and role of women. Important to create, maintain and engage in formal spaces for dialogue. Abstract: This paper systematically reviews the evidence on what capacities the state requires to leverage agriculture for nutrition in fragile contexts, maintaining a focus on state in South Asia (especially India). It uses the framework of what the state ought to do (in terms of pathways), can do (in relation to parts of the enabling environment it is able to deliver) and is willing to do (addressing constraints in terms of political choices). The results of the search were sorted into three further themes: capacity of the state to intervene systemically and intersectorally; engage with participatory and locally relevant understandings of agriculture-nutrition linkages, and to create, maintain and engage in formal spaces for dialogue.